Dopamine receptor agonists mechanism of actions on glucose lowering and their connections with prolactin actions - Chien, Hung-Yu; Chen, Su-Mei; Li, Wan-Chun (Frontiers in Clinical Diabetes and Healthcare, 2023)
Robust experiment evidence suggests that prolactin can enhance beta-cell proliferation and increase insulin secretion and sensitivity. Apart from acting as an endocrine hormone, it also function as an adipokine and act on adipocytes to modulate adipogenesis, lipid metabolism and inflammation. Several cross-sectional epidemiologic studies consistently showed that circulating prolactin levels positive correlated with increased insulin sensitivity, lower glucose and lipid levels, and lower prevalence of T2D and metabolic syndrome. Bromocriptine, a dopamine receptor agonist used to treat prolactinoma, is approved by Food and Drug Administration for treatment in type 2 diabetes mellitus since 2009. Prolactin lowering suppress insulin secretion and decrease insulin sensitivity, therefore dopamine receptor agonists which act at the pituitary to lower serum prolactin levels are expected to impair glucose tolerance. Making it more complicating, studies exploring the glucose-lowering mechanism of bromocriptine and cabergoline have resulted in contradictory results; while some demonstrated actions independently on prolactin status, others showed glucose lowering partly explained by prolactin level. Previous studies showed that a moderate increase in central intraventricular prolactin levels stimulates hypothalamic dopamine with a decreased serum prolactin level and improved glucose metabolism. Additionally, sharp wave-ripples from the hippocampus modulates peripheral glucose level within 10 minutes, providing evidence for a mechanistic link between hypothalamus and blood glucose control. Central insulin in the mesolimbic system have been shown to suppress dopamine levels thus comprising a feedback control loop. Central dopamine and prolactin levels plays a key role in the glucose homeostasis control, and their dysregulation could lead to the pathognomonic central insulin resistance depicted in the “ominous octet”. This review aims to provide an in-depth discussion on the glucose-lowering mechanism of dopamine receptor agonists and on the diverse prolactin and dopamine actions on metabolism targets.